PENENTUAN WAKTU STANDAR PENGGANTIAN OLI SHOCK DENGAN TsA-1 (TOOL SHOCK ABSORBER) DI BENGKEL PT. ASTRA INTERNATIONAL TBK-HONDA SALES OPERATION MATARAM - Suartika, I Made; Triadi, A.A. Alit; Yudhyadi, I G.N.K.; Sahram (Energy, Materials and Product Design, 2022)
Honda Sales Operation Mataram is a company engaged in distribution, retail and vehicle maintenance workshops. Existing workshops become a job for some communities and help improve the economy of the community. It is an important concern considering that it is the mechanics who are the main spears in service. From this, a company needs human resources that are able to work effectively and efficiently. To produce human resources that work effectively and efficiently, proper human resource planning and management is needed to encourage the achievement of the company’s vision and mission. In planning and managing time it is necessary to take measurements of working time and update existing resources or the need for a tool to accelerate the pace of productivity in the company. One of them is in the oil shock and seal shock changes, and made TsA-1 (shock absorber tool) to make it easier for mechanics to work and know the comparison of time in completing a job, where the normal time obtained by using ordinary tools in oil shock changes is 39.38 minutes and the normal time obtained using TsA-1 (shock absorber tool) in shock oil change is 33.52 minutes. So the mechanic is faster to do his job using TsA-1 (Tool shock absorber), where the time difference is 5.86 minutes. The standard time obtained using a regular tool is 41.45 minutes and the standard time using TsA-1 (tool shock absorber) is 35.28 minutes. Mechanics using the TsA-1 (shock absorber) tool are 6.17 minutes faster than regular tools. And for the replacement of seal shock obtained a normal time of 53.36 minutes with a regular tool, 51.70 minutes using TsA-1 (Tool shock absorber). Mechanics are faster to do their work in 1.66 minutes using TsA-1 (Tool shock absorber). The standard time of seal shock replacement with a regular tool is 56.16 minutes, and 54.42 minutes using TsA-1 (Tool shock absorber). Mechanics using TsA-1 (shock absorber) are 1.74 minutes faster than regular tools.